Developing and implementing 20-mph speed limits in Edinburgh and Belfast: mixed-methods study - Ruth Jepson; Graham Baker; Claire Cleland; Andy Cope; Neil Craig; Charlie Foster; Ruth Hunter; Frank Kee; Michael P Kelly; Paul Kelly; Karen Milton; Glenna Nightingale; et al. (NIHR Journals Library, 2022)
Background: Transport initiatives such as 20-mph (≈30-km/h) speed limits are anticipated to result in fewer road casualties and improve perceptions of safety, leading to increases in active travel. Lower speeds may also lead to more pleasant environments in which to live, work and play. Objectives: The main objective was to evaluate and understand the processes and effects of developing and implementing 20-mph speed limits in Edinburgh and Belfast. The focus was on health-related outcomes (casualties and active travel) that may lead to public health improvements. An additional objective was to investigate the political and policy factors (conditions) that led to the decision to introduce the new speed limits. Design: This was a mixed-methods study that comprised an outcome, process, policy and economic evaluation of two natural experiments. Setting: The study was set in Edinburgh, Scotland, and Belfast, Northern Ireland, from 2000 to 2018. Participants: The whole population of each city were participants, as well as stakeholders involved in implementation and decision-making processes. Intervention: The intervention was the implementation of 20-mph legislation, signage, enforcement, and education and awareness-raising in Edinburgh (citywide) and Belfast (city centre). Main outcome measures: The main outcomes measured were speed; number, type and severity of road collisions; perceptions; and liveability. Data sources: The following data sources were used - routinely and locally collected quantitative data for speed, volume of traffic, casualties and collisions, and costs; documents and print media; surveys; interviews and focus groups; and Google Street View (Google Inc., Mountain View, CA, USA). Results: Collisions and casualties - the overall percentage reduction in casualty rates was 39% (the overall percentage reduction in collision rates was 40%) in Edinburgh. The percentage reduction for each level of severity was 23% for fatal casualties, 33% for serious casualties and 37% for minor casualties. In Belfast there was a 2% reduction in casualties, reflecting differences in the size, reach and implementation of the two schemes. Perceptions - in Edinburgh there was an increase in two factors (support for 20 mph and rule-following after implementation) supported by the qualitative data. Liveability - for both cities, there was a small statistical increase in liveability. Speed - mean and median speeds reduced by 1.34 mph and 0.47 mph, respectively, at 12 months in Edinburgh, with no statistically significant changes in Belfast. History, political context, local policy goals, local priorities and leadership influenced decision-making and implementation in the two cities. Limitations: There was no analysis of active travel outcomes because the available data were not suitable. Conclusions: The pre-implementation period is important. It helps frame public and political attitudes. The scale of implementation and additional activities in the two cities had a bearing on the impacts. The citywide approach adopted by Edinburgh was effective in reducing speeds and positively affected a range of public health outcomes. The city-centre approach in Belfast (where speeds were already low) was less effective. However, the main outcome of these schemes was a reduction in road casualties at all levels of severity. Future work: Future work should develop a statistical approach to public health interventions that incorporates variables from multiple outcomes. In this study, each outcome was analysed independently of each other. Furthermore, population measures of active travel that can be administered simply, inexpensively and at scale should be developed. Study registration: This study is registered as ISRCTN10200526. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 10, No. 9. See the NIHR Journals Library website for further project information.